2011
DOI: 10.4012/dmj.2011-029
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite particle characteristics influence the enhancement of the mechanical and chemical properties of conventional restorative glassionomer cement

Abstract: The aims of this study were to improve the mechanical and chemical properties of conventional restorative glass ionomer cement (GIC) by adding hydroxyapatite (HAp) preparations with different characteristics, and to investigate the underlying reaction mechanisms. Fuji IX GP ® was used as the control GIC. The experimental GICs consisted of four HAp-particles with different characteristics added at 8 mass% to Fuji IX-powder. All cements were prepared by mixing with Fuji IX-liquid (P/L=3.6). Four HApparticles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 30 publications
(28 reference statements)
5
64
0
7
Order By: Relevance
“…7 On the downside, GIC is susceptible to dehydration and abrasion, and exhibits friability, reduced translucence, and technique sensitivity. 7,8 Cellulosic fibers were introduced to GIC by Silva et al, 9 who aimed to improve the mechanical strength of this promising restorative. In suitable proportions, cellulose fibers reinforced the composite without altering the working time and final setting time of the material.…”
Section: Introductionmentioning
confidence: 99%
“…7 On the downside, GIC is susceptible to dehydration and abrasion, and exhibits friability, reduced translucence, and technique sensitivity. 7,8 Cellulosic fibers were introduced to GIC by Silva et al, 9 who aimed to improve the mechanical strength of this promising restorative. In suitable proportions, cellulose fibers reinforced the composite without altering the working time and final setting time of the material.…”
Section: Introductionmentioning
confidence: 99%
“…This infiltration caused the compressive strength of the HApS particles to increase and become comparable to that of the GIC-S matrix. In contrast, the microcompressive strength of individual HApS particles is only about 0.6 MPa, which is extremely low compared to the value of approximately 180 MPa for fluoroaluminosilicate glass particles 20) . In addition, HAp also has the ability to not only adsorb but also release several substances 29,30) .…”
Section: Discussionmentioning
confidence: 77%
“…Recent reports of the addition of hydroxyapatite (HAp) into commercially prepared GIC showed improvement in the cement's mechanical properties, i.e., compressive and flexural strength [16][17][18] with good bonding and fluoride properties 17,19) . Moreover, our previous study demonstrated that the addition of HAp particles with highly reactive properties, such as a high specific surface area, can enhance the mechanical and chemical properties of conventional GIC for dental restoration 20) . The purpose of the present study was to evaluate the mechanical and chemical properties of a novel GIC containing porous HAp, referred to herein as apatite ionomer cement (AIC), as a pit and fissure sealant.…”
Section: Introductionmentioning
confidence: 99%
“…8 Hence, same concentration of hydroxyapatite was used in the present study to check the influence on the shear bond strength and micro hardness of GIC.…”
Section: Materials and Method:-mentioning
confidence: 99%